Benthic contribution to seasonal silica budgets in two macrotidal estuaries in North-Western France - Raimonet, Mélanie; Ragueneau, Olivier; Soetaert, Karline; Khalil, Karima; Leynaert, Aude; Michaud, Emma; Moriceau, Brivaela; Rabouille, Christophe; Memery, Laurent (Frontiers in Marine Science, 2023)
The paper aims to build seasonal silica budgets in two macrotidal estuaries, the Elorn and Aulne estuaries of the Bay of Brest (North-Western France), based on modeling and measurements, in order to increase our understanding of the silica (Si) cycle at land-sea interfaces. A diagenetic model was developed to quantify benthic Si fluxes, e.g. aSiO2 deposition fluxes that are difficult to assess through direct measurements. Sediment cores were also seasonally sampled at six stations to provide data essential to parametrize and validate the model. Vertical profiles of porosity, burrowing depth, biodiffusive coefficients, concentrations of amorphous silica (aSiO2) and silicic acid (Si(OH)4 and the proportion of reactive aSiO2 were measured. The results show that sites sampled along the Elorn and Aulne estuaries constitute significant net Si deposition areas (1-4.5 mmol Si m-2 d-1), particularly in the upstream during winter and in midstream and downstream during summer. Year round, reprecipitation is negligible (< 3%) while burial accounts for the retention of 30-80% of deposited aSiO2. In winter, burial dominates the benthic Si budget. As surface-integrated benthic Si fluxes are low compared to riverine aSiO2 fluxes, the Si export to coastal waters is high (93%) during winter. In contrast, in summer, burial accounts for 38% of river Si fluxes, and Si(OH)4 flux from the sediment is high as a result of enhanced benthic recycling and bioirrigation. Internal estuarine processes, e.g., benthic and pelagic primary production, dissolution and benthic Si fluxes, surpass river fluxes in magnitude during summer. Overall, we conclude that the Elorn and Aulne macrotidal estuaries are efficient filters of Si, retaining about 4-38% of river Si fluxes, and even 6-67% when accounting for retention in intertidal marshes, but with massive exports occurring during winter floods.